IDEALISME, RELATIVISME, DAN KREATIVITAS AKUNTAN - Immanuel Oky Nurcahyo; Nurmala Ahmar (The Indonesian Accounting Review, 2012)
Creativity and ethics have been the crucial factors that attract attention. These two factors are very important for the researchers to be researched recently. This study tries to find out the influence of idealism and relativism towards the accountants creativity. This took a controllable variable of job tenure and ages, and the variable of accountants, as the sample, were indicated by the gender and GPA. This main sample was mainly of the accountants in Surabaya and a controllable sample i e undergraduate accounting students at STIE Perbanas Surabaya. It employed the technique that is questionnaires distributed to the respondents. The analysis was conducted by using multiple regression analysis. Based on the data analysis; it was found that that idealism, of relativism, and job tenure affected the creativity. However, the age, gender, and GPA were found that they didnt influence the creativity.